2009
DOI: 10.1016/j.ejcnurse.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Uptake of Cardiac Rehabilitation: Using Theoretical Modelling to Design an Intervention

Abstract: A theoretically worded letter and leaflet could be an inexpensive intervention to improve attendance at cardiac rehabilitation. The letters and leaflets will now be evaluated in a randomised trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Thus, the CSM provides a framework for the development of theory-based behavior change interventions that lead to the effective translation of intentions and motivation into actual behavior [19]. The CSM has been used to develop interventions for diabetes [18], asthma [18], and attendance for cardiac rehabilitation [20]. For example, a CSM theory-based letter and information leaflet have been successfully shown to improve cardiac rehabilitation attendance [20].…”
Section: Csm Theoretical Framework For Changing Perception Of Dentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the CSM provides a framework for the development of theory-based behavior change interventions that lead to the effective translation of intentions and motivation into actual behavior [19]. The CSM has been used to develop interventions for diabetes [18], asthma [18], and attendance for cardiac rehabilitation [20]. For example, a CSM theory-based letter and information leaflet have been successfully shown to improve cardiac rehabilitation attendance [20].…”
Section: Csm Theoretical Framework For Changing Perception Of Dentmentioning
confidence: 99%
“…The CSM has been used to develop interventions for diabetes [18], asthma [18], and attendance for cardiac rehabilitation [20]. For example, a CSM theory-based letter and information leaflet have been successfully shown to improve cardiac rehabilitation attendance [20]. …”
Section: Csm Theoretical Framework For Changing Perception Of Dentmentioning
confidence: 99%
“…Details of the interventions and their development are described elsewhere 16 Dear, Your consultant and health team have recommended that you undergo an eight-week cardiac rehabilitation program, which aims to help you to recover and improve your health and life. The program is multidisciplinary, which means that the doctor, cardiac rehabilitation nurse, dietician, physiotherapist and the occupational therapist work together to tailor the program to meet your individual needs.…”
Section: The Interventionsmentioning
confidence: 99%
“…The fact that nearly 20% of those who agreed to attend a session at a particular time never attended a single meeting indicates a substantial problem frequently observed in health service delivery and clinical trials that individuals do not attend scheduled appointments. Recently, several studies have shown that inexpensive theory based intervention based on simple planning interventions, letters or leaflets may be effective in improving attendance [53], [54] and for the present line of research it might be sensible to explicitly add an intervention focussing on attendance to the first meeting in order to improve participation. For those participants who attended at least one meeting, the intervention was found to be highly acceptable as indicated by intervention retention and material completion.…”
Section: Discussionmentioning
confidence: 99%